Multiscale Pore Architecture and Its Influence on Porosity, Permeability, and Fluid Flow in Tight Gas Reservoirs of the Shihezi H8 Formation, Ordos Basin - Muhammad Toseef Adnan; Guishan Zhang; Bin Chang; Hu Wei; Ren Peng; Wang Chang; Liang Wang (Energies)
Characterizing pore network morphology and its influence on critical reservoir properties such as porosity, permeability, and fluid flow pathways is imperative for maximizing production from tight gas sandstone reservoirs. This study integrated petrographic and pore-scale analyses to investigate diagenetic effects on the Shihezi H8 Formation, Ordos Basin, China. Sixty core plug samples spanning depositional facies from wells were analyzed using thin-section petrography, scanning electron microscopy, laser grain size analysis, mercury injection capillary pressure (MICP), nuclear magnetic resonance (NMR), and porosity–permeability measurements. Thin-section observations indicated that formation primarily comprises litharenite and sub-litharenite sandstones deposited in fluvial–deltaic environments composed primarily of quartz and feldspar grains. Diagenesis caused significant porosity reduction through initial mechanical compaction, 3–13% quartz cementation, and localized dissolution, resulting in secondary porosity of up to 5%. Three diagenetic facies were differentiated based on variations in mineralogy and diagenetic alterations. MICP classified pore networks into three reservoir types defined by mean throat radii ranging from 0.091 to 0.270 μm. NMR distinguished pore architectures as uniformly microporous, bimodally micro–mesoporous, and heterogeneously distributed multiscale pores. Larger throat radii correlated positively with higher porosity (up to 8.6%), gas porosity (10.5%), and permeability (0.1911 mD). Grain size analysis demonstrated a positive correlation between mean detrital grain diameter (>2.6 φ, 0.18 mm, (180 µm)), and significantly elevated average porosity (5–8%) compared to finer lithologies, implying depositional energy and sorting regimes. Integrating depositional features, diagenetic alterations, and multiscale pore architecture characterization quantitatively and qualitatively enhanced predictions of heterogeneity in hydrocarbon flow behavior amongst these tight reservoirs. The optimized insights from this integrated study provide a framework to guide development strategies and field appraisal methods for maximizing recovery from unconventional tight gas formations.